Historical Parallels to the Destruction at the Time of the Crucifixion - Tvedtnes, John A. (Journal of Book of Mormon studies, 1994)
To the nonbeliever, the wide variety of destructive forces unleashed in the New World at the time of Christ's crucifixion seems preposterous or, at the very least, unscientific. The account in 3 Nephi 8-9 mentions the simultaneous occurrence of earthquake, fire, strong winds, extensive flooding, the complete burial of cities, and thick darkness. An examination of known great natural disasters in historical times reveals that the Book of Mormon in no way exaggerates. All of the destructive forces mentioned in 3 Nephi 8-9 can be readily explained in terms of the tectonic forces that result from the encounter of the plates on which the continents and the oceans lie. The complex variety of destructive forces that we normally consider to be separate phenomena of nature is, in reality, strong evidence for the historicity of the Book of Mormon account.